High-temperature digital image correlation techniques for full-field strain and crack length measurement on ceramics at 1200°C: Optimization of speckle pattern and uncertainty assessment. (November 2021) - Kaczmarek, Robert; Dupré, Jean-Christophe; Doumalin, Pascal; Pop, Octavian; Teixeira, Lucas; Huger, Marc
Highlights: Preparation of optimized speckle pattern on ceramic samples for high temperature measurements. Characterization of speckle patterns and evaluation of DIC uncertainty using a mechanical device at high temperature. Improvement of DIC uncertainty by varying some DIC parameters and by using image pre-processing. Measurement of crack length within refractories at high temperature by using 2P-DIC (2-Parts DIC). Abstract: High-temperature mechanical tests coupled with Digital Image Correlation (DIC) on ceramics which exhibit rather low level of strain require to overcome extreme experimental conditions that usually can reduce significantly measurement accuracy. Thermal resistance of speckle pattern, black body radiation and heat haze are three main concerns, which should thus be taken into account while designing a high-temperature image acquisition setup. In this aim, an experimental procedure has been specifically designed in order to minimize the three above-mentioned disturbances. The main objective of this study is to select a suitable high-temperature resistant speckle pattern for mechanical characterization at 1200 °C (or above) on refractory ceramics. Most of tested speckle patterns were performed with white alumina adhesive and dark ceramic grains (silicon carbide or brown fused alumina). Different grain sizes of silicon carbide were tested. At first, different speckle patterns are compared in terms of DIC strain measurement uncertainty by discussing speckle features, some main DIC parameters and two image pre-treatments (low pass filter, image size reduction). Then, these speckle patterns are tested to analyse fracture behaviour of refractories through a Brazilian test. An enhanced digital image correlation technique (2P-DIC), dedicated to monitor the fracture behaviour, is applied to study the evolution of crack length. The best representation of crack progression has been achieved for sample surface covered with a fine SiC powder ranging from 50 to 100 µm. It is then possible to compare the fracture behaviour between 1200 °C and 20 °C and to show that the refractory exhibits more crack branching at 1200 °C in comparison with behaviour at room temperature.